Utilizing online database system among undergraduate students - Zulkifli, Zahidah; Azlan, Nor Athira; Mohammad Daud, Nur Hidayah; Samsuri, Suhaila; Hussin, Husnayati; Md Ali, Asma (Academic World, 2016)
Undergraduate students are generally required to produce their coursework assessment work with research writing quality by using valid academic sources that are available on the library online databases. Studies discover that most undergraduate students rely too much on general Internet resources. The dependency on these Internet resources signifies that they lack skills in securing online information from other valid academic resources. It also indicates their lack of awareness on the importance of obtaining the desired information from valid sources conveniently. This scenario has led to the underutilization of university’s information facilities among undergraduate students who form the majority in university. Therefore, this research mainly focuses in investigating how online databases could be of assistance and useful particularly among undergraduate students for their learning and research purposes. It shall promote the use of online databases as well as propose a conducive electronic environment for the students. A series of interviews with the administrative officers of current online database system were conducted together with the study of the current practice of doing research among undergraduate students. As a result, an Ishikawa diagram has been developed that is representing the causes of the usage of online database system among undergraduate students and the additional features for online database system has been discovered that can support the tasks of learning and research. The evaluation of a proposed framework will be followed by a prototype in order to inculcate research skills among undergraduate students. This study shall improve the undergraduates’ skill in searching for academic sources, increase their awareness in evaluating the source of information obtain and consecutively expand the utilization of online databases subscribed by the university.